Fullerene-pyropheophorbide a complexes as sensitizer for photodynamic therapy: Uptake and photo-induced cytotoxicity on Jurkat cells - Rancan, Fiorenza; Helmreich, Matthias; Mölich, Andreas; Jux, Norbert; Hirsch, Andreas; Röder, Beate; Witt, Christian; Böhm, Fritz (Journal of Photochemistry and Photobiology B-Biology, 2005)
The main challenge in searching for new photosensitizers is to improve their specificity for target cells to avoid toxicity towards normal cells. New modular drug delivery systems were proposed consisting of a multiplying unit with the property of carrying several drug moieties and an addressing unity with high selectivity for target cells. Following this concept, two new fullerene-bis-pyropheophorbide a derivatives were synthesized: a mono-(FP1) and a hexa-adduct (FHP1). The photophysical characterization of the compounds revealed significantly different parameters related to the number of addends at the fullerene core. In this study, the derivatives were tested with regard to their intracellular uptake and photosensitizing activity towards human leukemia T-lymphocytes (Jurkat cells) in comparison with the free sensitizer, pyropheophorbide a. The C -hexa-adduct FHP1 resulted to have a significative phototoxic activity (58% dead cell, after a dose of 400 mJ/cm , 688 nm) while the mono-adduct FP1 had a very low phototoxicity and only at higher light doses. The photosensitizing activity of the fullerene hexa-adduct, FHP1, resulted to be lower than that of pyropheophorbide a. The lesser intracellular concentration reached by the C -hexa-adduct FHP1 is probably the reason for its lower phototoxicity with respect to pyropheophorbide a. © 2005 Elsevier B.V. All rights reserved.